MEMBANGUN KARAKTER MELALUI IMPLEMENTASI TEORI BELAJAR MENURUT ALIRAN PSIKOLOGI GESTAL BERBASIS KECAKAPAN ABAD 21 - Ena Suma Indrawati (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2019)
Gestalt Psychology is a flow of psychology that studies a phenomenon as a whole or totality, the data in Gestalt psychology are called phenomena (symptoms). Phenomenon is the most basic data in Gestalt Psychology. In this case Gestalt Psychology agrees with the philosophy of phenomonology which says that an experience must be seen in a neutral way. In a phenomenon there are two elements, namely objects and meanings. Object is something that can be described, after being captured by the senses, the object becomes an information and at the same time we have given meaning to the object. Keywords: character, psychology, gestalt, 21st century skills